Developing Self-Awareness and Cultural Understanding in Cross-Cultural Counseling - Robbi Asri; Firman; Yarmis Sukur; Rendy Amora (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2024)
Cross-cultural counseling is becoming increasingly important in an increasingly diverse global society. This study explores the importance of self-awareness and cultural understanding in cross-cultural counseling practice. Self-awareness refers to the counselor’s ability to understand and manage their own values, beliefs, and biases, while cultural understanding involves in-depth knowledge of the client’s cultural background and how it influences their perspectives and experiences. This article highlights strategies and approaches that counselors can use to enhance self-awareness and cultural understanding, including ongoing education and training, self-reflection, and the application of culturally sensitive communication principles. By developing strong self-awareness and cultural understanding, counselors can provide more effective and inclusive support to clients from diverse cultural backgrounds, improve counseling outcomes, and strengthen the therapeutic relationship. The method used is a literature review with critical analysis of ongoing research on the specific topic.